EFEKTIVITAS ANTIBAKTERI BAWANG PUTIH (Allium sativum L) SEBAGAI PENGAWET ALAMI PADA IKAN LELE DUMBO (Clarias gariephinus) SEGAR - Dyah Anggraeni; Nurlela Nurlela (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2019)
Background: Natural preservatives are compounds produced by natural ingredients that can suppress bacterial growth and development. Natural preservatives are carried out because most of the preservatives circulating are chemicals and unsafe for the body. One of the natural preservatives is by using garlic extract (Allium sativum L).  Objective: This study is aimed to determine the effectiveness of the antibacterial garlic (Allium sativum L) as a natural preservative in fresh African catfish (Clarias gariepinus).  Method: This research used the Pour Plate iroculation method. African catfish (Clarias gariepinus) which is soaked with garlic (Allium sativum L) with a concentration of 7%, 14% and 21% for 30 minutes, then the fish will be kept at room temperature with a storage period of 24 hours and 48 hours and calculated growth in bacterial numbers with the Colony counter.  Result: Based on the research result, it was found that garlic extract (Allium sativum L) can obstruct the effectiveness of antibacterial in African catfish (Clarias gariepinus) at a concentration of 14%.